ANALISIS LEADING INDICATOR KEBIJAKAN MONETER DALAM MENGATASI KEMISKINAN DI 5 NEGARA ASIA TENGGARA - Sari, Wahyu Indah; Nasution, Lia Nazliana; Novalina, Ade (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This study analyzes the effectiveness of monetary policy on poverty. Where the purpose of this study is to see the effectiveness of the variables of economic growth, inflation, money supply, interest rates and exchange rates in alleviating poverty. The problem that has existed so far is the lack of precise policies used in alleviating poverty. However, this study predicts the ability to use monetary policy in dealing with the problem of poverty. There are five countries that will be studied, namely Laos, Indonesia, the Philippines, Myanmar and Thailand. Data analysis to see leading indicators by country uses the ARDL Panel method. The data source used is secondary data from the Worldbank. In analyzing the data in this study using Software Eviews 10. The results of the ARDL Panel analysis research note that the interest rate and money supply variables can be leading indicators (Laos, Indonesia, Philippines, Myanmar and Thailand), but their position is unstable in short run and long runs. The main leading indicator of the effectiveness of monetary policy that is able to become a leading indicator of Laos, Indonesia, the Philippines, Myanmar and Thailand in overcoming poverty is the exchange rate variable as seen from the short run and long run stability. Where the exchange rate variable in the short term and long term is significant in overcoming poverty.